Case Report: Acute Ehrlichia canis induced Severe Hepatitis and Its Management in a Fijian Dog - Yogeswaranthan, Prashanth (Media Kedokteran Hewan, 2026)
A four-year-old female spayed Boerboel dog presented with a three-day history of reduced appetite, lethargy, dark tarry watery faces, high fever, and dark urine in September 2024. General Clinical Examination (GCE) revealed that pyrexia, pale to slightly icteric mm, and infestation with brown ticks on the body, especially inter digital region and ear pinna. The clinical signs suggested a tick-borne disease. Blood samples were submitted to the laboratory for biochemistry and Full Blood Count (FBC), and serological testing by using a commercial test kit.  Laboratory tests ALP (Aspartate Aminotransferase, ALT Alanine Aminotransferase, AST aspartate transferase, Total Bilirubin, and GGT gamma-glutamyl transferase revealed severe pancytopenia with elevation of hepatic enzymes. Serological test positive for Ehrlichia canis antibodies. This diagnosis was acute ehrlichiosis with secondary hepatic impairment. Treatment included doxycycline at a dose rate of 10mg/kg body weight once daily for 28 days, liver supportive therapy with Denamarin® 1 tab once a day for 28 days, and Frontline® spot-on covering tick infestation and supportive with vitamin B complex and high-density commercial nutrition supplement. The dog significantly recovered from E. canis infection after 28 days of therapeutic medical support. This is the first reported incidence of canine E. canis in the Fiji Islands.